Implementation The Indonesian Government Policy Of The Ministry’s Strategic Plan By KEMENPAREKRAF /BAPAREKRAF 2020 -2024 During The COVID-19 Pandemic In Banyuwangi Regency - Aditya Wiralatief Sanjaya; Rudi Tri Handoko; Esa Riandy Cardias (Innovative: Journal Of Social Science Research, 2023)
This research examines the implementation of the Ministry of Tourism and Creative Economy's strategic targets in Banyuwangi, which was chosen as the first district to implement new-normal tourism activities in 2020. The Ministry has 11 strategic targets mapped into 4 perspectives, namely stakeholders, customer, internal process, and learning & growth. The first perspective has 1 strategic target, while the second perspective has 6 strategic targets. The third perspective has 3 strategic targets, and the fourth perspective has 1 strategic target. Qualitative research was used to analyze the condition of the scientific object, where the researcher served as the key instrument, and data reduction was conducted by comparing the ministry's strategic plan and the performance evaluation of the Banyuwangi government in the tourism sector.